PENGARUH PEMBERIAN DOSIS VAKSIN AI (Avian Influenza) INAKTIF PADA ITIK BETINA TERHADAP TITER ANTIBODI YANG DIHASILKAN - Winddi Amelia; Purnama Edy Santosa; Sri Suharyati (JURNAL ILMIAH PETERNAKAN TERPADU, 2016)
The aim of research was to knowing AI vaccine doses in female ducks of the most well titer of antibodies produced. The research was conducted in Desember 2015 in Sabah Balau, District Tanjung Bintang, District South lampung. Ducks uses were 54 tails are a female using a completely randomized design (RAL) consisting of 6 treatments (P0: control with distilled water provisison, P1: administration of inactivated AI vaccine doses of 0,1 ml, P2: of inactivated AI vaccine doses of 0,2 ml, P3:of inactivated AI vaccine doses of 0,3 ml, P4: of inactivated AI vaccine doses of 0,4 ml, and P5: of inactivated AI vaccine doses of 0,5 ml) with repeat 3 times.  The result of analysis of variance showed that the level of AI vaccine doses at 5 days old female ducks no significant (P>0,05) on antibody titer to the value of each row (P0 : 4,33, P1 : 4,33, P2 : 7,33, P3 : 4,67, P4 : 4,33, P5 : 5,7). Keywords: Antibody Titer, Avian Influenza, Doses of Vaccine, Female Ducks